Family Business Continuance: A Review for Future Research - Annisa Ramadanti; Nyayu Lathifah Tirdasari; Wawan Dhewanto (Business Review and Case Studies, 2021)
The process of changing leaders from the previous leaders to the recent leaders is a critical moment in family business continuance. The complex issue of succession needs an in-depth understanding of researches. This paper's objective was to review several works of literature with regards to succession in the family business. Moreover, this study discovered future research potentials concerning family business succession. This study reviewed, summarized, and combined the past and extant works of literature. China, Malaysia, Pakistan, Slovenia, and Tunisia emerged as the locus of study. This study performed a review using keywords of family business and succession to look for a comprehensive database. This study found that each country has a different culture in doing their family business succession. The most influential factor was the belief of the predecessor. For instance, the Chinese families were following Confucian rules, the Pakistani and Malaysian families were following Islamic laws, and the predecessors influenced the Tunisian families in involving their children in their family business. Meanwhile, the first generation still dominated the family business in Slovenia without any succession plan. The results show opportunities for a new research agenda. First, the comparison of family business succession between various ethnic groups. Second, the reason(s) for a family business to not set its succession plan. Keywords: business continuance, family business research, literature review, succession